Changes in the structure of information processes in society: opportunities and challenges in the future - Eskaraev Talgat (Zien Journals, 2021)
The article analyzes the thoughts about the information web. The main signs of the information web are revealed. A number of proposals on the problems associated with the introduction of advanced information technologies are considered
Keywords: the value of information; informatization; industrial society; post-industrial society